2016
DOI: 10.1007/s13198-016-0496-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance modeling of the serial processes in refining system of a sugar plant using RAMD analysis

Abstract: The main objective of this paper is to present a method to identify the critical component of the system. As traditionally, any one parameter among availability, reliability and maintainability parameters is computed to identify the critical component and its effect on performance of the system. In this paper, reliability, availability, maintainability and dependability (RAMD) parameters or indices are computed to identify the critical component of the system. Mathematical modeling of the system based on Marko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The high value of dependability ratio represents the necessity of maintenance. Aggarwal et al [24] mentioned that the dependability value increases if availability is above 0.9 and decreases if availability is less than 0.1. The minimum value of dependability is given by:…”
Section: Dependabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The high value of dependability ratio represents the necessity of maintenance. Aggarwal et al [24] mentioned that the dependability value increases if availability is above 0.9 and decreases if availability is less than 0.1. The minimum value of dependability is given by:…”
Section: Dependabilitymentioning
confidence: 99%
“…Sinha and Mukhopadhyay [23] carried out failure analysis of jaw crusher and its components using ANOVA methodology. Aggarwal et al [24] developed a mathematical model for performance evaluation of the serial processes in refining system of a sugar plant using RAMD analysis. Aggarwal et al [25] suggested a mathematical model and analyzed fuzzy availability of serial processes in the crystallization system of a sugar plant.…”
Section: Introductionmentioning
confidence: 99%
“…e proposed results identified the critical subsystem in the milk powder production system with concerning variation in the values of major maintenance parameters [16]. Identifying the utmost critical operation in the tunnel boring systems in mixed ground conditions has been illustrated, and the RAMD of the individual tunnel boring operations in mixed ground conditions is obtained with the application of the Markov chain process [17]. Performance modeling of the refined systems in the sugar plant has been presented through the application of the Markov birth-death approach.…”
Section: Introductionmentioning
confidence: 99%
“…Maintainability is a design factor that decides the degree to which a product allows safe, quick and easy replacement of its component parts. Design for maintainability refers to designing the system to find the optimum balance between capital cost and ongoing maintenance cost (Barabadi et al 2010;Tortorella 2015;Tsarouhas 2015;Garmabaki et al 2016a;Gharahasanlou et al 2017;Kumar et al 2017;Aggarwal et al 2017). Design for maintainability needs to consider human ergonomics, logistics management, design layout, the level of experience and training of maintenance personnel and so on (Knezevic 1993;Naseri and Barabady 2016).…”
Section: Introductionmentioning
confidence: 99%